Impact of interactive multimedia (IMM) on students' mathematics achievements - Shiratuddin, Norshuhada; Ibrahim, Haslinda; Hassan, Shahizan; Ismail, Salina (Universiti Utara Malaysia, 1998)
Universiti Utara Malaysia (UUM) students’ performance in mathematics course has always been discouraging. Many students obtained low CGPA results because of poor mathematics grades. This project focused on solving this problem through the implementation of new teaching method: Interactive Multimedia course ware (IMM) Apart from trying to solve the problem, this project also intends to find answer to the question of whether IMM has positive impact on UUM students’ achievements. A course ware was developed and tested in labs. It is hoped that with the introduction of the multimedia course ware, students might find it useful and act as a personal tutor. Overall indications were negative. There was no significant evidence that IMM leads to positive impact on students’ achievements.